2020
DOI: 10.1037/emo0000531
|View full text |Cite
|
Sign up to set email alerts
|

Feeling excited or taking a bath: Do distinct pathways underlie the positive affect–health link in the U.S. and Japan?

Abstract: Feeling good is linked to better health in Western contexts. Recent studies show, however, that the affect-health link is not consistent across cultures. We suggest two reasons for such inconsistency. The first follows from research showing that North American (versus East Asian) cultures tend to value high arousal positive (HAP) states, e.g., excited, more than low arousal positive (LAP) states, e.g., calm. The second is one we propose for the first time. Positive affective experience is manifest in internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…The results partially supported our hypotheses that high-arousal positive affect would show weaker association with health than general/low-arousal positive affect in Japan, except for functional health. These are consistent with prior research showing that low-arousal positive affect was more strongly associated with health than high-arousal positive affect in Japan (Clobert et al, 2019). Cumulative profiles of hedonic well-being did not predict change in health symptoms, contrary to eudaimonic well-being.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results partially supported our hypotheses that high-arousal positive affect would show weaker association with health than general/low-arousal positive affect in Japan, except for functional health. These are consistent with prior research showing that low-arousal positive affect was more strongly associated with health than high-arousal positive affect in Japan (Clobert et al, 2019). Cumulative profiles of hedonic well-being did not predict change in health symptoms, contrary to eudaimonic well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Yoo et al (2017) found that positive affect predicted healthy lipid profiles in the United States, but not in Japan. Clobert et al (2019) suggest that cultural moderation of the association between positive affect and health might be particularly strong for high-arousal positive affect. Their findings, in fact, showed that high-arousal positive affect predicted selfreported health more strongly in the United States than in Japan, while low-arousal positive affect even showed a reversed pattern (Clobert et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…All items were scored on a 5‐point Likert‐type scale, ranging from 1 (never) to 5 (always). Positive and negative affect measure in this questionnaire was validated previously 29 . The scores from each of the 18 items were averaged and used for analyses (Cronbach's α values: 0.95 [positive] and 0.92 [negative]).…”
Section: Methodsmentioning
confidence: 99%
“…Positive and negative adjectives were measured by four and five items of each (e.g., enthusiastic, attentive, proud, active, afraid, jittery, irritable, ashamed, upset) from The Positive and Negative Affect Schedule (PANAS) [33], which is a widely used mood measurement and regarded as one of the indicators of hedonic well-being. In addition, positive affect was each measured by six items (i.e., cheerful, in good spirits, extremely happy, calm and peaceful, satisfied, full of life), because such low arousal positive feeling has been reported to have stronger link with health among Japanese people, other than high arousal feelings, measured by PANAS [34]. The negative affect was also measured by an original six-item scale consisting one item on "nervousness" from PANAS and items from other sources (i.e., so sad nothing could cheer you up, restless or fidgety, hopeless, that everything was an effort, worthless).…”
Section: Positive and Negative Affect/adjectivementioning
confidence: 99%
“…We used these four sub-scales as a measurement of affect to keep their independent construction. Positive affect and adjective in this questionnaire is well validated elsewhere [34].…”
Section: Positive and Negative Affect/adjectivementioning
confidence: 99%